Presentation of Doctor José Emilio G. Araujo, Director General of the Inter-American Institute of Agricultural Sciences at a session of the International affairs section of the adult education association - Instituto Interamericano de Ciencias Agrícolas (IICA) (Instituto Interamericano de Ciencias Agrícolas (IICA), 2021)
22 páginas.